ESTIMATE OF WELFARE LOSS FROMMARKET POWER IN UKRAINIAN ECONOMY - A. Gerasymenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article investigates and improves the methodology of estimate of welfare loss from market power. Basing on the improved methodology the author estimates such a loss in Ukrainian economy of 2008-2011.